Biology of cloned cytotoxic T lymphocytes specific for lymphocytic choriomeningitis virus: clearance of virus in vivo. - Byrne, J A (J Virol, 1984)
Our data show that 1 X 10(7) to 1.5 X 10(7) lymphocytic choriomeningitis virus-specific, H-2-restricted cloned cytotoxic T lymphocytes (CTL) administered intravenously into acutely infected mice totally cleared virus from the spleens (10(4) to 10(5) PFU per spleen reduced to less than 50 PFU per spleen) by 24 h. This activity was genetically restricted in that cloned CTL could reduce titers of infectious virus in syngeneic C57BL/6 mice but not allogeneic BALB/c mice. Dose-response analysis indicated that at least 3 X 10(6) to 5 X 10(6) cloned CTL injected intravenously were needed to reduce significant amounts of infectious virus in the spleens. No infectious virus could be recovered from the spleens for at least 4 days after injection of cloned CTL. Hence, CTL play a major role in elimination of infectious virus from spleens during lymphocytic choriomeningitis virus infection. Our results also indicate that cloned CTL propagated in vitro for long periods of time can mediate a biologically relevant effect in vivo. These cells should be of considerable value in defining the precise manner in which CTL bring about control of viral infection, analyzing lymphocyte trafficking, and the potential use of cloned CTL in immunotherapy against viral disease.